Impact of technology on Cold Chain - Shahid, Muhammad Ahsan (2019)
In this era of rapidly changing technology, the traditional ways of how businesses operate have evolved. The digitalization and data monitoring techniques have certainly affected almost all industries. This paper looks at the technological impacts on cold chain. The cold chain is basically the transportation of temperature sensitive products. This study will explore the cold chain from origin to destination. Temperature monitoring is an essential part of the cold chain in order to maintain the integrity of the products. The integrity could be compromised even if there is a slight temperature breach. Due to integrity, various advanced temperature maintaining, and monitoring devices and methods have entered the market such as Radio Frequency Identification (RFID) and Wireless Sensor Monitoring, Pallet covers, Artificial Intelligence and Blockchain. All of these methods and devices have been studied extensively before, except for Blockchain. This paper will explore the use cases of blockchain in the supply chain and especially cold chain. The focus will also be on the ‘last mile’ aspect, which is the final leg of the transportation journey. The research was completed with the help of secondary data that was published online, and primary data using the interviews of people who had blockchain and cold chain experience. The study concludes that blockchain provides security to the data from the temperature monitoring devices and it makes the tracking of the temperature-sensitive products easier. The study also concludes that the last mile aspect has been augmented with the help of current technology, but it could be optimized with the help of artificial intelligence. This study will help the cold chain and supply chain professionals who want a deeper insight into how blockchain could be useful within their specific field.